Interpersonal Communication Role in Cross-Sector Collaboration: A Case Study of Look Communication and BCA - Siti Aminatus Zahro; Past Novel Larasaty (Ilomata International Journal of Social Science, 2026)
Look Communication, a creative agency specializing in event management and strategic communication, has maintained a long-term cross-sector collaboration with PT Bank Central Asia Tbk (BCA), a leading financial institution in Indonesia, for nearly a decade. Despite the longevity of this partnership, the collaboration frequently encounters challenges arising from the contrasting organizational disciplines and cultures between the creative and financial sectors. As this dyad remains underexplored, particularly in the Indonesian context, this study offers a new empirical perspective on cross-sector collaboration dynamics. This study explores the strategic role of interpersonal communication in facilitating effective cross-disciplinary collaboration between the two entities. Employing a qualitative intrinsic case study design, data were collected through in-depth interviews with key stakeholders, including a Senior Account Executive and the Director of Look Communication, a client representative from BCA, and an independent public relations practitioner for triangulation. The analysis reveals that Joseph A. DeVito’s five elements of interpersonal communication provide an analytical framework for understanding how trust, mutual understanding, and sustained interaction are developed and maintained. These elements openness, empathy, supportiveness, positivity, and equality form the core of the interpersonal communication in cross-sector collaboration and enable deeper insights into how trust and shared understandings emerge through everyday interactions. Furthermore, the Client-Firm Relationship model proposed by Pritchard and Smith underscores the importance of sustained communication in fostering trust and cooperation. The findings suggest that interpersonal communication functions not only as a mechanism for sustaining long-term professional relationships but also as a strategic foundation for managing organizational differences and enhancing collaborative effectiveness.